Penerapan Model Pembelajaran ASSURE Melalui Media Papan Warna Bersusun Untuk Meningkatkan Pemahaman Konsep Matematis Siswa di SDN Dukuh 01 Pagi Jakarta Timur - Kirana, Kaila Sashi; Amelia, Winda (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2025)
Elementary school is the beginning for students to acquire important knowledge in life. This study addresses the low interest of students in mathematics subjects due to learning dominated by traditional learning models. This study aims to determine the improvement in students' understanding of mathematical concepts in multiplication material in grade III at SDN Dukuh 01 Pagi by implementing the ASSURE learning model using Stacked Color Board media. This classroom action research was conducted on 28 students in two cycles, namely Cycle I and Cycle II, using the Kemmis and Taggart models. Data were collected using interviews, observations, and tests. In the last cycle, the average student achievement reached 50.07%, increasing significantly to 66.24% in Cycle I and 85.05% in Cycle II. In the application of the ASSURE learning model, this occurs naturally because in the learning process, colored boards are used. This makes students more interactive and active in the learning process so that it can have a significant impact on improving elementary school students' understanding of mathematical concepts.